Justiça e trabalho precarizado: um estudo sobre as condições de trabalho em Vitória da Conquista - Lopes, Sebastião Martins (2014)
The precarization of labor has been a remarkable phenomenon in recent decades and has affected the lives of workers in all sectors whether private or public. This trend is determined by capitalism, globalization and technological advances that cause changes in the production structure reorganizing the labor market. This study focuses primarily on analyzing the precarious working relationship and its consequences in the City of Vitória da Conquista - Bahia. To achieve the proposed objective for the study, research is a bibliographic nature. Thus, the study revealed that the process of precarization of labor in Vitória da Conquista is the result of a mass migration from the countryside to the city and also the surrounding towns. The search for the unconscionable profits contributes to this situation. The rights of these workers are exploited and usurped improving numerous lawsuits. But many workers are subjected to poor working conditions to be your source of income and survival.